Antimicrobial and anti-endotoxin activity of N-acetylcysteine, calcium hydroxide and their combination against Enterococcus faecalis, Escherichia coli and lipopolysaccharides - Rayana Duarte Khoury; Amjad Abu Hasna; Carolina Fedel Gagliardi; Renata Marques de Melo Marinho; Cláudio Antonio Talge Carvalho; Eduardo Bresciani; Marcia Carneiro Valera (PeerJ, 2024)
Background The management of endodontic infections is a complex challenge, mainly due to the involvement of diverse microorganisms and their by-products. This study aimed to evaluate the efficacy of N-acetylcysteine (NAC), calcium hydroxide (Ca(OH)2), and their combined application as intracanal medications in combating Enterococcus faecalis, Escherichia coli, and lipopolysaccharides (LPS) from E. coli. Methods A total of 60 single-rooted human teeth were carefully selected and divided into six groups. These tooth canals were deliberately exposed to E. faecalis (ATCC 29212) and E. coli (ATCC 25922) to induce biofilm formation. Subsequently, the specimens were treated with NAC, Ca(OH)2, or a combination of both substances. Three samples of the root canals were collected at three moments: the first sample (S1) was to confirm the initial contamination, the second sample (S2) was immediately post-instrumentation, and the third sample (S3) was collected after the use of the intracanal medication. The antimicrobial efficacy of these intracanal medications was assessed by enumerating colony-forming units per milliliter (CFU/mL). In addition to this, the kinetic chromogenic Limulus Amebocyte Lysate (LAL) assay by Lonza was used to quantify LPS from E. coli. Data tested for normality; then, Kruskal-Wallis and Friedman tests were used, and Dunn’s for multiple comparisons. Results The findings of this study showed significant reductions in the microbial load of E. faecalis and E. coli by S3. Notably, there were no statistically significant differences among the treatment groups concerning these microorganisms. However, it was observed that only the combination of NAC and Ca(OH)2 led to a noteworthy decrease in the quantity of E. coli’s LPS after 7-days, demonstrating a statistically significant difference from the other treatment groups. NAC + Ca(OH)2 combination, applied for a duration of 7-days, proved to be more suitable in reducing the presence of E. faecalis, E. coli, and LPS from E. coli within the context of endodontic infections.